2010
DOI: 10.1590/s1519-69842010000500006
|View full text |Cite
|
Sign up to set email alerts
|

Living together, sometimes feeding in a similar way: the case of the syntopic hylid frogs Hypsiboas raniceps and Scinax acuminatus (Anura: Hylidae) in the Pantanal of Miranda, Mato Grosso do Sul State, Brazil

Abstract: taxonomically and thus, also tend to share physiological and behavioural traits (see Menin et al., 2005). Therefore, a clear understanding of the relationship on niche overlap, similarity and competition among species is necessary to answer questions on community structure (Lawlor, 1980). IntroductionSyntopic related species are expected to be exposed to a similar array of potential prey, especially if they share activity period, body size and microhabitat features (e.g. Pianka, 1986;Sluys and Rocha, 1998; Gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…The high importance of agile arthropods such as beetles, crickets, grasshoppers, ants and spiders in the diet of species of the Leptodactylus genus indicate more sit-and-wait feeding strategy (Maneyro et al 2004, Rodrigues et al 2004, Sanabria et al 2005, De-Carvalho et al 2008, Solé et al 2009). However, in some of these studies there is great quantity of larvae or more sedentary groups, which suggest an opportunistic feeding Biota Neotrop.,vol.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The high importance of agile arthropods such as beetles, crickets, grasshoppers, ants and spiders in the diet of species of the Leptodactylus genus indicate more sit-and-wait feeding strategy (Maneyro et al 2004, Rodrigues et al 2004, Sanabria et al 2005, De-Carvalho et al 2008, Solé et al 2009). However, in some of these studies there is great quantity of larvae or more sedentary groups, which suggest an opportunistic feeding Biota Neotrop.,vol.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the most important orders in the diet of L. fuscus found in this study and De-Carvalho et al (2008) can be attributed to opportunistic behavior and differences in prey availability, so that the diet composition is determined by the food availability of arthropods in environments occupied by the population (Das 1996, Hirai & Matsui 2000, Hirai 2004, Lopez et al 2007. Several studies found a relationship between predator and prey size or prey number, based on stomach contents (Maneyro et al 2004, Biavatti et al 2004, Sanabria et al 2005, López et al 2007). In general this relationship is attributed to the fact that larger frogs have larger heads and therefore can eat larger prey, which is evident when assessing the diet of young and adult individuals (Solé & Rödder 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations